Cadmium Speciation Distribution Responses to Soil Properties and Soil Microbes of Plow Layer and Plow Pan Soils in Cadmium-Contaminated Paddy Fields - Hao, Xiaodong; Bai, Lianyang; Liu, Xueduan; Zhu, Ping; Liu, Hongwei; Xiao, Yunhua; Geng, Jibiao; Liu, Qianjin; Huang, Lihua; Jiang, Huidan (Frontiers in Microbiology, 2021)
Cadmium (Cd) speciation ratio in arable land determines the Cd exposure risk and Cd uptake in crops. However, the driving mechanisms of Cd speciation change on the vertical scale of paddy fields remain poorly understood. In this study, the effects of plow layer and plow pan on Cd speciation distribution were investigated in a long-term Cd-contaminated rice ecosystem. The Cd accumulative effect within rice grain was enhanced with high levels of activated Cd speciation ratios in soils. Activated Cd speciation ratios were higher in plow layer soils, while stabilized Cd speciation ratios were elevated in plow pan soils. Soil physicochemical properties and soil microbes synergistically affected the Cd speciation changes in different ways between the two soil layers. Soil pH and organic elements in plow layer environment directly hindered the transformation of stabilized Cd speciation, while in plow pan environment, soil pH and organic elements indirectly decreased activated Cd speciation ratios, and resulted in the accumulation of stabilized Cd speciation via regulating the predominant bacterial taxa. This study will improve our understanding of how soil environments regulate Cd speciation distributions in rice ecosystems, and help to seek effective remediation methods of Cd-contaminated paddy fields to reduce the Cd accumulation in rice.